2021
DOI: 10.1111/bph.15657
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of migraine: Drug classes, mechanisms of action, clinical trials and new treatments

Abstract: Migraine is the sixth most prevalent disease globally, a major cause of disability, and it imposes an enormous personal and socio‐economic burden. Migraine treatment is often limited by insufficient therapy response, leading to the need for individually adjusted treatment. In this review, we analyse historical and current pharmaceutical development approaches in acute and chronic migraine based on a comprehensive and systematic analysis of Food and Drug Administration (FDA)‐approved drugs and those under inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 153 publications
(209 reference statements)
0
48
0
1
Order By: Relevance
“…The involvement of glial cells in migraine has been addressed in several studies and hypotheses (e.g., [ 130 , 131 , 132 ]), but mainly in the context of the role of glial cells in cortical-spreading depression. The action of antagonists of and antibodies against CGRP and its receptor also affects glial cells expressing the CALCA gene, but the problem of epigenetic regulation of this gene as a target in migraine prevention and therapy is still a perspective [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of glial cells in migraine has been addressed in several studies and hypotheses (e.g., [ 130 , 131 , 132 ]), but mainly in the context of the role of glial cells in cortical-spreading depression. The action of antagonists of and antibodies against CGRP and its receptor also affects glial cells expressing the CALCA gene, but the problem of epigenetic regulation of this gene as a target in migraine prevention and therapy is still a perspective [ 133 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic susceptibility factors differ between migraine with and without aura ( Pisanu et al, 2017a ). Other risk factors comprise concomitant psychological and psychiatric disorders ( Pisanu et al, 2020 ), hormonal status, myofascial syndromes, and the influence of various adverse environmental factors, including nutritional factors or stressful situations ( Chai et al, 2014 ; Pisanu et al, 2017b ; Marmura, 2018 ; Zobdeh et al, 2021 ). Numerous studies have identified a variety of factors that can trigger migraine attacks.…”
Section: Important Types Of Headaches—disease Burden Clinical Forms A...mentioning
confidence: 99%
“…However, headache patients react differently to given drugs leading to a wide variety of treatment responses. It is estimated that only 50% of migraine patients adequately respond to acute and preventive therapy ( Pomes et al, 2019 ; Zobdeh et al, 2021 ). Likewise, many patients with cluster headache fail to respond adequately to pharmacological treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…51 CGRP has been looked at as a potential target for migraine treatment as far back as the 1980s. 52 Early studies found levels of CGRP to be elevated during migraine when measured in external jugular blood. 53 CGRP levels normalized with treatment with the migraine-specific rescue medication, sumatriptan.…”
Section: Onabotulinumtoxinamentioning
confidence: 99%